Philosophia perennis - Schmidt-Biggemann, Wilhelm. author. aut Link
XX, 506 p.
Keywords: The study features the five most important and most efficacious themes of Western spirituality in their ancient historical origins and in their unfolding up to early modernity: Divine names, Microkosmos-Makrokosmos, theories of creation, the idea of spiritual spaces, and the concepts of eschatological history.